The Influence of Fear of Missing Out on Impulsive Buying Behaviour in Generation Z UPI Tasikmalaya: Case Study of TikTok Shop Users - Natadilaga, Arya Abdillah; Fauziyah, Azizah; Yusup, Ismail (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The expansion of social commerce has reshaped consumer decision-making, particularly among Generation Z as digital natives who are highly engaged with social media platforms. TikTok Shop integrates entertainment, social interaction, and instant purchasing features that may intensify psychological stimuli such as Fear of Missing Out (FOMO), thereby encouraging impulsive buying behavior. This study investigates the level of FOMO and impulsive buying among Generation Z students at Universitas Pendidikan Indonesia (UPI) Tasikmalaya who use TikTok Shop, and empirically examines the effect of FOMO on impulsive buying behavior. Employing a quantitative descriptive-verificative design, data were collected through structured questionnaires from 339 respondents selected using purposive sampling. Simple linear regression analysis was applied to test the proposed hypothesis. The findings reveal that Fear of Missing Out has a positive and statistically significant effect on impulsive buying behavior among Generation Z TikTok Shop users. This indicates that psychological concerns related to social exclusion and trend avoidance play a critical role in accelerating unplanned purchasing decisions within digital commerce environments. The study contributes empirical evidence to consumer behavior research in social commerce contexts and highlights the importance of understanding psychological drivers in shaping responsible consumption and effective digital marketing strategies.